Makassar City's New Social Movement Based on Literacy (Paradigma Institute Makassar Case Study) - Amsal, Bahrul; Sunaniah; Mappe, Ulfa Utami (Indonesian Journal Publisher, 2024)
Social movements are characterized by collectivity that acts based on a common goal. Until now, situations deemed less than ideal have sparked the emergence of social movements. The Paradigma Institute Makassar is a semi-formal organization that promotes change based on literacy issues. The literacy movement of the Paradigma Institute, viewed through the lens of new social movements, aims to foster social change by exploring social change issues through transformative actions like social science study classes, writing classes, and book discussion forums. The primary goal of this writing is to examine the connection between literacy issues and social change by analyzing social movements and program models that promote social change, all within the framework of the Paradigma Institute's vision as a new social movement. This research uses a qualitative descriptive approach. We conduct data analysis through three stages: data reduction, data presentation, and conclusion drawing. The research findings reveal two main points. First, the Paradigma Institute is a semi-formal organization that operates based on a new social movement model to realize its vision and mission, including the aim of producing an enlightened society. Second, the change actions, such as social science study programs, writing classes, and book discussions, concretize the changes the organization pursues. In this digital era, Paradigma Institute also has the opportunity to expand its impact through the use of information technology, in the form of an organizational website, thus enabling broader and more sustainable social transformation.